A role for the peripheral immune system in the development of alcohol use disorders?. (1st August 2017) - de Timary, Philippe; Stärkel, Peter; Delzenne, Nathalie M.; Leclercq, Sophie
Abstract: Preclinical studies have largely supported that alcohol-consumption induces the development of an important neuro-inflammation and this neuro-inflammation contributes to alcohol-drinking behaviors, notably through TLR4 and LPS related mechanisms. The neuro-inflammation originates from a direct interaction of ethanol with the neuronal and immune brain cells, but also from the generation of an inflammation at the periphery. Ethanol in particular interacts with the intestine to develop a gut dysbiosis and an increase in gut permeability, that allows the liberation of bacterial fragments to the systemic circulation and induces a pro-inflammatory response in the systemic circulation and peripheral organs, and in particular the liver. Peripheral cytokines or activated peripheral cells may cross the blood-brain barrier and activate neuro-inflammation. In humans, peripheral inflammation and intestinal dysbiosis are related to symptoms of alcohol use disorders (AUD), such as depression, anxiety and alcohol-craving, However, the dysbiosis, could also participate in a different manner to the symptomatology of the addiction, possibly by interacting with the stress system, by interfering with the sleep processes and altering the abilities for social interactions. The role of the gut suggests that interventions with probiotics or prebiotics might in the future be of interest for the treatment of the addiction. This article is part of the Special Issue entitled "Alcoholism". Highlights: A review on peripheral sources of inflammation in AUD is proposed. The intestine appears as a major source of peripheral inflammation. Other peripheral sources of inflammation like the gut-wall or the liver are also suggested. Mechanisms for transduction of peripheral inflammation to the CNS are evoked. Hypotheses regarding the relation between peripheral inflammation and the symptoms of AUD is are described.